Sonic hedgehog is basolaterally sorted from the TGN and transcytosed to the apical domain involving Dispatched-1 at Rab11-ARE - Sandoval, Lisette; Labarca, Mariana; Retamal, Claudio; Sánchez, Paula; Larraín, Juan; González, Alfonso (Frontiers in Cell and Developmental Biology, 2022)
Hedgehog (Hh) secretion from apical and/or basolateral domains occurs in different epithelial cells impacting development and tissue homeostasis. Palmitoylation and cholestyrolation attach Hh proteins to membranes and Dispatched-1 (Disp-1) promotes their release. How these lipidated proteins are handled by the complex secretory and endocytic pathways of polarized epithelial cells remains unknown. We show that polarized MDCK cells address newly synthesized sonic hedgehog (Shh) from the TGN to the basolateral cell surface and then to the apical domain through a transcytosis pathway that includes Rab11-apical recycling endosomes (Rab11-ARE). Both palmitoylation and cholesteroylation contribute to this sorting behavior, otherwise Shh lacking these lipid modifications is secreted unpolarized. Disp-1 mediates first basolateral secretion from the TGN and then transcytosis from the Rab11-ARE. At steady state, Shh predominates apically and can be basolaterally transcytosed. This Shh trafficking provides several steps for regulation and variation in different epithelia, subordinating the apical to the basolateral secretion.